The Effect of Work Climate and Leader Traits on Teacher Job Satisfaction Jambi City State High School - Firman Firman (Journal of Accounting and Finance Management, 2020)
The purpose of this study is to examine the direct influence of the work climate and the characteristics of leaders on job satisfaction of teachers in Jambi City Public High School. This study uses a quantitative approach with the research subjects of SMA Negeri 1 Jambi City, SMA Negeri 3, SMAN Negeri 4, and SMA Negeri 5 Jambi City with a sample of 63 students. The instrument used for data collection in the form of a list of questions or questionnaire. Data collected from respondents were then processed using path analysis. Before carrying out statistical analysis, the data must meet the requirements of the analysis prerequisite tests that will be used. The tests were the normality test, linearity test, homogeneity test. The results showed that the work climate had a significant effect on job satisfaction in the amount of 12.2% with a significance level of 0.005. The nature of leadership has a significant effect on job satisfaction in the amount of 10.3% with a significance level of 0.009. If teacher job satisfaction reaches a percentage level of 100%, then 10.3% is contributed by the nature of leadership. Work climate and leadership characteristics have a significant effect on job satisfaction in the amount of 14.4% with a significance level of 0.009. If teacher job satisfaction reaches a percentage level of 100%, then 14.4% is contributed by the work climate and the nature of leadership.